Quasi-static finite-difference time-domain simulation of a pulse induction metal detector - Saydam, Talha (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2018)
Bu tezde, Maxwell denklemi tabanlı Kuvazi-Statik Zaman-Uzayı Sonlu-Farklar (KS-ZUSF) yöntemi ile üç boyutlu Kartezyen koordinatlarda darbe indüksiyonlu bir metal detektörünün tespit başarımı zaman uzayında incelenmiştir. Kaynak işareti olarak dikdörtgen darbe dalga fonksiyonu kullanılmıştır. Sayısal problem uzayı ikinci mertebeden geliştirilmiş Mur tipi Soğurucu Sınır Koşulu uygulanarak sonlandırılmıştır. Düşük kayıplı bir ortamdaki iletken bir kürenin frekans imzası hesaplanarak yöntemin doğruluğu gösterilmiştir. Küp şeklindeki gömülü metal ve hava boşluğu için zaman imzaları farklı senaryolar için hesaplanmıştır. Böylece, gömülü cisimlerin tespiti ve sınıflandırılması için temel bilgi elde edilmiştir.

In this thesis, detection performance of a pulse induction metal detector is investigated with Maxwell's equations based Quasi-Static Finite-Difference Time-Domain (QS-FDTD) method in three dimensional Cartesian coordinates. The type of source is rectangular pulse wave which is generated by a magnetic dipole antenna. The numerical problem space is terminated with second order modified Mur Absorbing Boundary Condition. The solution is validated with a canonical problem of frequency signature calculations of a conducting sphere in a weakly lossy medium. The time signatures of buried metallic and air cubes are calculated for the different scenarios. Therefore, the fundamental knowledge is obtained for the detection and classification of the buried objects.
Darbe indüksiyonlu bir metal dedektörünün kuvazi-statik zaman-uzayı sonlu-farklar benzetimi
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering